Institutionalizing a transdisciplinary approach to technology development in a Bangladeshi NGO. (4th August 2014) - Zweekhorst, Marjolein B.M.; Broerse, Jacqueline E.W.; Bunders, Joske F.G.
Transdisciplinary research is a recent trend within interdisciplinary research that not only crosses disciplinary boundaries but also integrates academic and non–academic knowledge. Although rather difficult to apply, it is highly appropriate for solving complex environmental and societal problems. This paper reviews the conditions needed for successful transdisciplinary research and outlines one such approach: the Interactive Learning and Action (ILA) approach. Attempts to institutionalize the ILA approach in an agricultural development organization in Bangladesh - the Grameen Krishi Foundation - and the adaptations made to the approach during the process, provided interesting lessons for the further development of transdisciplinary research methodology.